2023
DOI: 10.5194/nhess-23-1335-2023
|View full text |Cite
|
Sign up to set email alerts
|

Review article: Design and evaluation of weather index insurance for multi-hazard resilience and food insecurity

Abstract: Abstract. Ensuring food security against climate risks has been a growing challenge recently. Weather index insurance has been pointed out as a tool for increasing the financial resilience of food production. However, the multi-hazard insurance design needs to be better understood. This paper aims to review weather index insurance design for food security resilience, including the methodology for calculating natural hazards' indices, vulnerability assessment, and risk pricing. We searched for relevant research… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 85 publications
0
0
0
Order By: Relevance
“…Insurance helps to maintain economic stability, especially for vulnerable societies [22]. However, due to its volatility in weather conditions, many insurers stopped covering disasters such as floods [5].…”
Section: Provision Of Insurance For Small-scale Farmersmentioning
confidence: 99%
See 2 more Smart Citations
“…Insurance helps to maintain economic stability, especially for vulnerable societies [22]. However, due to its volatility in weather conditions, many insurers stopped covering disasters such as floods [5].…”
Section: Provision Of Insurance For Small-scale Farmersmentioning
confidence: 99%
“…Inspired by the importance of predictability and the emergence of machine learning, Cesarini, Figueiredo [31] suggested integrating multiple sources of weather data then applying supervised machine learning (ML) techniques, such as support vector machines and artificial neural networks (ANNs) to classify impacts of drought and floods in the Dominican Republic between 2000 and 2019. The study of Benso, Gesualdo [22] examined weather indices in Brazil and how those affect soybean farms: they argued that disasters could be interrelated and proposed a multi-hazard risk assessment approach. During the 2023 United Nations Climate Change Conference, the former secretary of the United States, Hillary Clinton, indicated that she is pioneering new reforms of the insurance industry by working with the Arsht-Rock Foundation Resilience Center to recognize parametric insurance as a form of climate change resilience [3].…”
Section: Provision Of Insurance For Small-scale Farmersmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of premium rates for index-based crop insurance has been discussed to a limited extent in the literature. In rare studies addressing this issue, damages are modeled using indices, and the pure premium is calculated based on historical index values rather than actual losses (Benso et al, 2023).…”
Section: Introductionmentioning
confidence: 99%